The socio-cultural significance of mineral licks to the Maijuna of the Peruvian Amazon: implications for the sustainable management of hunting - Gilmore, Michael P. (J Ethnobiol Ethnomed, 2020)
BACKGROUND: The overhunting of wild species is a major threat to biodiversity in the Amazon; yet, managed, sustainable hunting is widely considered part of the solution to conserving wildlife populations. Hunting is both a culturally important activity for Indigenous people and provides an important food source. Mineral licks, a focal point of hunting in Amazonia, are naturally occurring areas in the forest where animals come to obtain essential minerals or clays that are thought to neutralize plant-based alkaloids. We sought to better understand the socio-cultural importance of mineral licks to the Maijuna Indigenous group to inform the sustainable management of this habitat and associated wildlife populations. METHODS: Semi-structured interviews, focus groups, and participatory mapping were carried out with hunters to assess the significance of mineral licks and their associated animal resources as well as to determine how the relationship that the Maijuna have with mineral licks has changed over time. RESULTS: Mineral licks are culturally significant and useful to the Maijuna in a variety of ways. Hunters target these areas year-round both during the day and night, and animals killed are consumed for subsistence and sold to generate income. The spatial use of mineral licks across the landscape is determined on the generational family level, with families maintaining exclusive use of selected mineral licks and excluding access by other hunters. The Maijuna also have traditional beliefs for why animals visit mineral licks, which is linked to the traditional Maijuna story of the creation of the first tapir. The relationship that the Maijuna have with mineral licks has changed considerably over time, which is observed through changes in hunting technologies and methods as well as the loss of traditional knowledge and beliefs. CONCLUSIONS: Traditional and current Maijuna hunting conventions, in which families maintain exclusive use of selected mineral licks, likely reduce the probability of overexploitation of animal populations. Community-based management plans for mineral licks in Maijuna lands and beyond must incorporate and account for the multiple cultural and economic needs of local communities while also striving toward ecological sustainability. Country-wide strategies to conserving forests and using them sustainably should aim to ensure land tenure for rural peoples and encourage management that incorporates traditional sustainable hunting conventions.